The Perfusion Features of Recurrent Hepatocellular Carcinoma After Radiofrequency Ablation Using Contrast-Enhanced Ultrasound and Pathological Stemness Evaluation: Compared to Initial Tumors - Wu, Jin-Yu; Bai, Xiu-Mei; Wang, Hong; Xu, Qian; Wang, Song; Wu, Wei; Yan, Kun; Yang, Wei (Frontiers in Oncology, 2020)
Objective: To investigate the perfusion features of local recurrence of hepatocellular carcinoma (HCC) after radiofrequency ablation (RFA) with contrast enhanced ultrasound (CEUS) and pathological correlation, as well as to compare with the initial HCC. Methods: From 2010 to 2018, 42 patients had recurrent HCC after RFA were enrolled in this study. The initial HCC patients included 32 males and 10 females with the an average age 58.2±8.1 years. CEUS imagines for initial HCC lesions and local recurrence after RFA were compared. The perfusion features were analyzed, including enhancement time, process, boundary, morphology, washout time, washout degree, feeding vessels, internal necrosis. The H&E staining and CD133/ EpCAM staining was performed with biopsy samples for stemness study. Results: According to CEUS, 59.5% of initial HCC lesions had centripetal enhancement, and 61.9% of recurrent HCC lesions represented homogeneous enhancement at arterial phase (p<0.001). 73.8% of initial HCC had well defined margins at the peak, and 81.0% of recurrent HCC had poorly-defined margins (p<0.001). 78.6% of initial HCC were regular in morphology at the peak and 83.3% of recurrent HCC were irregular (p<0.001). The feeding vessels were more frequently found in initial HCCs (71.4%) than in recurrent HCCs (38.1%, p=0.002). In the late phase, 60% of initial HCCs had marked wash out while 83.3% of recurrent HCCs had marked wash out (p=0.019). 31.3% of the initial HCC had internal necrosis areas while only 7.1% of recurrent HCC had internal necrosis areas (p=0.035). In tumor size of 3-5cm, the washout time in recurrent HCC was shorter than that in initial HCC group (50.3±13.5s vs. 75.6±45.8s, p=0.013). Pathological staining displayed that the tumor stem cell markers (CD133 and EpCAM) were both highly expressed in recurrent samples compared with the initial tumors (CD133+: 19% vs. 5%, p=0.002; EpCAM+:15% vs. 6%, p=0.005). Conclusions: Recurrent HCC after RFA had more homogeneous enhancement with poor define border, marked wash out as well as less feeding vessels and inner necrosis compared to initial HCC. The stemness study also found upregulated stemness in recurrent HCC. These specific features might be related to its aggressive biological behavior.